A NOVEL PLANAR ELECTROCHEMICAL CELL FOR VOLTAMMETRIC MEASUREMENTS IN THIN HYDROGEL FILMS - KÉKEDY NAGY, László; GARAY, Fernando; LINDNER, Ernő (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The fabrication of a planar micro electrochemical cell is presented. The simplicity and the relative low cost of this kind of cells make them very interesting and promising in the development of chemical and biochemical sensors. The utilization of microelectrodes as working electrodes in planar electrochemical cells is preferred to the conventional macro electrodes because microelectrodes can be used in highly resistive media, have short response time, and excellent signal to noise ratio. In electrochemical sensor applications, the microelectrode surfaces are commonly modified with multiple layers to boost selectivity, control sensitivity, or to provide a biocompatible interface between the sensor and its environment. In this work, the fabricated set of bundled electrodes is covered with a hydrogel as an example of its potential use as electrochemical gas sensor. All micro electrochemical cells were characterized by cyclic voltammetry (CV) and the results were analyzed with different statistical methods.